Analysis of Argumentation in Surah Ad-Duha Based on Olivier Reboul's Argumentative Model (Journal of the College of Languages (JCL), 2025)
Influencing others and persuasion in human dialogues is an active and prominent element. Thus, argumentation is one of the distinctive aspects of these dialogues. In other words, argumentation is one of the uses of language to persuade the audience. In this context, rhetoric plays a crucial role in the structure of discourses as it is linked to the use of language and styles related to the situation and conditions of sentence formation. From this perspective, rhetoric is not merely a tool for producing texts but rather one of the important tools for creating a horizon of vision for language and various discourse issues. By examining stylistic phenomena and studying their relationship with different levels of perception, the researcher in the field of rhetoric discovers the hidden psychological, cultural, and social layers of the text. One of the approaches to the analysis of argumentation is Olivier Reboul's rhetorical argumentation approach, which considers the rhetorical aspect in any discourse as something that makes that discourse persuasive, and this occurs through the unity of form and content. In this article, we aim to analyze the different levels of Surah Ad-Duha according to Reboul's model. The research findings show that in Surah Ad-Duha, all three pictorial sections of Reboul's model have been employed in line with the argumentative goal of the surah. At the phonetic level, there is a close relationship between sounds and connotations, which can be observed in the rhymed endings of the surah. In the structural images section, the use of elements such as ellipsis, oath, emphasis, and fronting and postponement has successfully contributed to achieving the argumentative goal of the surah.